(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Today, the modern education system faces the need to educate highly qualified, ambitious, competitive, enterprising, spiritually and physically healthy individuals. In this regard, the development of the pedagogical personality and the formation of pedagogical competence in future educators are considered to be of paramount importance. It should not be forgotten that high professional competence is not only the level of knowledge, but also the practical skills, experience and personal qualities of the employee. The management competence of educators is characterized by such criteria as teamwork, leadership, cooperation, mentoring, and the use of official authority.